Prestasi Belajar Di Era Digital - Hana Kamila Putri; Christian Wiradendi Wolor; Marsofiyati (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
This research was conducted to determine the influence of Teacher Competency (X1), Learning Facilities (X2) on the Influence of Learning Achievement (Y). This research used quantitative methods with a sample of 100 respondents. The data analysis technique uses SmartPLS (Partial Least Square) software version 4.0.9.2. The results of this research show that: 1) Teacher competency has a positive and significant effect on learning achievement. 2) Learning facilities have a positive and significant effect on learning achievement. 3) Teacher competency and learning facilities have a positive and significant effect on learning achievement.